Taguchi approach to erosion wear optimization of WC-10Co-4Cr sprayed austenitic steel subjected to equisized slurry. Issue 9 (25th September 2018) - Singh, Gurmeet; Kumar, Satish; Sehgal, Satbir S.
Abstract : Purpose: This paper aims to optimize the erosion wear analysis of slurry impeller material. Stainless steel (SS-410) was used as the pump impeller material. This erosion test was established to influence the rotational speed, solid concentration, time period and particle size. Fly ash was used as the erodent material. Design/methodology/approach: The erosion wear experiments were performed at different particle size, rotational speed, time duration and solid concentration (by weight). These tests were performed at four different speeds of 750, 1, 000, 1, 250 and 1, 500 rpm, and the time durations of these experiments are 75, 120, 165 and 210 min. For protective coating, high-velocity oxygen-fuel spray process was used for depositing WC-10Co-4Cr coating on stainless steel. To investigate the influence of controlled process parameters on slurry erosion wear of pump impeller material, Taguchi method was used. Findings: Results show that significant improvement in erosion wear resistance has been observed by using WC-10Co-4Cr coating. The process parameters affecting the erosion wear loss were in following order: time > rpm > concentration > particle size. The means of signal-to-noise ratio of stainless steel SS410 with and without coating vary from 93.56 to 54.02 and from 86.02 to 48.18, respectively. Originality/value: For the erosion wear rate of both uncoated and coated stainless steel, the most powerful influencing factor was identified as time. The erosion test reveals that the coating exhibits ductile erosion mechanism and shows better erosion wear resistance (approximately two times) compared to uncoated stainless steel.